HOW POLLS ARE CONDUCTED - Aigneren, Miguel (La Sociología en sus Escenarios, 2010)
Abstract. Public opinion polls would have less value in a democracy if the public - the very people whose views are represented by the polls didn’t have confidence in the results. This confidence does not come easily. The process of polling is often mysterious, particularly to those who don’t see how the views of 1,000 people can represent those of hundreds of millions. Resumen. Los sondeos de opinión pública podrían tener mayor confiabilidad y validez para el ciudadano común si se les explicasen acertadamente el porqué mil personas entrevistadas pueden representar la opinión de miles de ellos.